Analisis Keterampilan Guru dalam Mengadakan Variasi pada Pembelajaran PAI di SDIT 1 Daarussalaam Sangatta - Nur Aidila Fitria; Muhammad Yoga Julyanur; Muhammad Zuhdi Hibatullah; Faelasup Faelasup (Lembaga Pengembangan Kinerja Dosen, 2024)
The ability of a nation to progress depends on its level of education. The quality of human resources produced is influenced by how good the quality of education is. Therefore, teachers play an important role in ensuring the success of education. Teachers' skills in teaching are key in creating meaningful learning for students. This research is intended to understand the teacher's skills in organizing learning variations, especially in Islamic Religious Education (PAI) subjects at SDIT 1 Daarussalaam Sangatta. The research method used is a qualitative approach of field research type through data collection from observation, interviews, and documentation. The results of the study highlighted the importance of variations in teaching styles, the use of media and learning tools, as well as communication patterns of interaction with students in order to create a comfortable and conducive learning atmosphere. The findings show that variation in learning plays a key role in motivating learners and teachers have an important role in ensuring such variation through three main components, especially in PAI learning at SDIT 1 Daarussalaam, namely variation in teaching styles that can be used by developing existing learning methods to be more varied and involve more activities for learners, the use of IT-based learning media and tools, and communication patterns of interaction with learners that can be done with many-way communication. Learning variations not only make teaching and learning activities more interesting but also facilitate better understanding for learners in order to achieve the desired learning objectives